Treatment of Adolescent Hallux Valgus With Percutaneous Distal Metatarsal Osteotomy. Issue 3 (June 2021) - Kotlarsky, Pavel; Gannot, Gil; Katsman, Alexander; Eidelman, Mark
Background . Hallux valgus is a complex deformity of the first ray of the foot, and a significant number of adolescents develop this deformity. More than 130 surgical procedures have been described to treat hallux valgus, but there is no compelling evidence to prefer one method over another. Minimal invasive techniques have been proposed and reported to be successful and cost-effective. The objective of this study was to describe the clinical course of adolescent patients treated with percutaneous distal metatarsal osteotomy. Methods . A retrospective study included patients who had a percutaneous hallux valgus correction during the years 2008 to 2015. The following measurements were compared before surgery up to last follow-up: AOFAS Hallux-Metatarsophalangeal-Interphalangeal questionnaire and radiological measurements (HVA, IMA, DMAA). Any postoperative complications were extracted from the medical records. Results . The procedure was performed on 32 feet (27 patients). All patients were <18 years of age. There were 10 male patients (12 feet) and 17 female patients (20 feet). Average age at surgery was 15.8 years (range = 13-18 years). Average follow-up time was 43 months (range= 24-94 months). The average AOFAS score before surgery was 66, and after surgery, at last follow-up was 96. This difference was significant (P value <.0001). Most patients were pain free after the procedure and returned to appropriate age functioning. Significant improvement was noted in all radiological criteria. Conclusions . Percutaneous distal metatarsal osteotomy is safe, reliable, and effective for the correction of mild to moderate symptomatic hallux valgus in adolescents. Levels of Evidence: Level IV